JURIDICAL RECONSTRUCTING OF MEDICAL DATA PROTECTION IN MACHINE LEARNING TO FULFILL THE RIGHT TO HEALTH - Dyah Nur Sasanti; Megawati Barthos (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2026)
The use of machine learning in the health sector has significantly changed the way medical personal data is managed and utilized. This technology improves the quality of health services, but at the same time poses a risk of violations of the right to health and the right to privacy due to algorithmic bias, lack of transparency, and weak data governance. This research aims to analyse the position of the right to health as a binding norm in the framework of medical personal data protection in Indonesia and to formulate an inclusive juridical reconstruction to mitigate risks. The research method used is normative juridical with a laws and conceptual approach, through the study of legal materials that collected by literature studies. The results of the study show that although the 1945 Constitution of Republic Indonesia, the Health Law, the PDP Law, and the ITE Law have provided a strong normative basis, there are still gaps due to the lack of specific regulations regarding algorithm audits, human rights impact assessments, and independent oversight. In conclusion, it is necessary to reconstruct regulations and strengthen supervisory institutions so that digital health innovations can apply in a fair, inclusive, and in line with the principles of non-discrimination. The author recommends to the Government to prepare regulations regarding the technical implementation of medical personal data protection, health service practitioners and digital health technology providers apply the principles of privacy by design and security by default, and encourage academics and legal researchers to develop studies about it.